INFLUENCE OF CADMIUM CITRATE LOW DOSES ON RAT EMBRYO’S CARDIOGENESIS - Nefyodova, O.O.; Yeroshenko, G.A.; Zadesenets, I.P.; Shatorna, V.F.; Nefyodov, O.O.; Kuznetsova, O.V. (World of Medicine and Biology, 2019)
Cadmium is one of the few toxic heavy metals, which physiological function in the human body is not established so far. Cadmium exhibits its toxic effects at very low concentrations and has acute and chronic effects on the body health. The purpose of the study was to experimentally determine the effect of cadmium citrate low doses on morphometric parameters of the embryonic heart, atrial-ventricular valves and coronary vessels with intragastric administration to pregnant female rats. The dose of cadmium citrate was 1.0 mg/kg of body weight. It has been experimentally determined that the effect of cadmium citrate at a given dose results in the reduced endocardial cushions volume of the atrial-ventricular channel and the reduced cardiofetal index in rat embryos. At the same time the growth of the coronary arteries diameter by 11.3% was observed.